WHEN WEIGHT DETERMINES CHILDBIRTH CHOICES: A DESCRIPTIVE STUDY OF OBESE PREGNANT WOMEN AT REGIONAL HOSPITAL DR. H. ABDUL MOELOEK OF LAMPUNG - Juwita Desri Ayu; Sugiarto (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Obesity in mothers is a major worldwide health issue that significantly raises the need for obstetric procedures, especially cesarean sections. Numerous difficulties for both mothers and newborns have been linked to elevated pre-pregnancy and gestational body mass indexes (BMI). The purpose of this study is to characterize the distribution of delivery methods among pregnant women who are obese at Dr. H. Abdul Moeloek Regional Hospital in Lampung Province, Indonesia. Total sampling was used to perform a quantitative, descriptive retrospective analysis. 58 pregnant women with a BMI of 30 kg/m² or above who gave birth between 2017 and 2023 were included. SPSS version 27.0 was utilized for data analysis. Findings out of the 58 instances that could be analyzed, 69.0% of obese pregnant women gave delivery via cesarean section, 27.6% gave birth spontaneous vaginally, and 3.4% had a vacuum induction. The majority (31.0%) were between the ages of 35 and 39, and 77.6% were multiparous. The type of delivery was found to be strongly influenced by maternal age, parity, and obesity. Being obese greatly raises the risk of having a cesarean section, especially for older and multiparous women. Reducing needless cesarean rates and improving mother and newborn outcomes may be possible with early treatments such as lifestyle modification education, prenatal counseling, and BMI-based risk assessment.